ANALYSIS OF COMMUNITY BEHAVIOR IN THE CASHLESS ERA OF THE NON-CASH PAYMENT SYSTEM IN MAKASSAR CITY - Sri Handila Mirwan; Anas Iswanto Anwar; Sri Undai Nurbayani (Jurnal Ekonomi, 2023)
This study aims to determine the factors that influence the people of Makassar city in conducting non-cash transactions. These factors consist of convenience, trust, lifestyle, risk, and cost. The data used in this study is primary data obtained directly from respondents using a questionnaire of 214 respondents using a Likert scale calculation. Respondents selected in this research are people who have monthly income or salaries, both public and private employees, with the category of permanent and non-permanent employees. The analytical method used is multiple linear regression with the SPSS analysis tool. Based on the analysis that has been carried out, the results show that partially the ease and risk variables have a positive and significant effect, while the trust and cost variables have a negative and significant effect, and the cost variable has no significant results. It can be stated in this study that there are four variables, namely Convenience, Trust, Risk, and Cost which have a significant influence together on the Non-Cash Transaction variable with a percentage level of 46%, while the remaining 54% is influenced by other variables.,